PERFORMANCE MODELING OF PLTU PAITON 1 WITH VARIATIONS IN MAIN STEAM PRESSURE, TEMPERATURE, AND CONDENSER PRESSURE USING GATECYCLE - Loasana, Okto Rosario Nisen; Iqbal, Muhammad; Soeparman, Sudjito; Yuliati, Lilis (International Journal of Mechanical Engineering Technologies and Applications, 2026)
Paiton Unit 1, 400 MW power plant, has been the subject of a detailed performance analysis utilizing modelling and simulation techniques employing GateCycle software. This study encompasses an evaluation of the impact of variations in main steam pressure, condenser pressure, and main steam temperature on key performance parameters, including thermal efficiency, heat rate, condenser duty, and power generation. The model underpinning this analysis was developed based on the heat balance scheme of Paiton Unit 1 PLTU, and its validity was confirmed through validation using operational data. The simulation results demonstrate that an increase in main steam pressure and temperature leads to enhanced thermal efficiency and output power of the plant, while an increase in condenser pressure results in reduced efficiency and net power generation. A decrease in condenser pressure increases the pressure difference between the turbine and condenser, thereby facilitating greater energy conversion to mechanical power. Heat rate analysis reveals that the heat rate value decreases with increasing main steam pressure and temperature and decreasing condenser pressure, indicating an increase in system efficiency. This study validates the hypothesis that optimization of key operational parameters at Paiton Unit 1 PLTU can enhance plant efficiency and reduce fuel consumption, thereby providing both technical and economic benefits.